VILLAGE FUNDS IMPLEMENTATION FOR BIRTH AND DEATH CERTIFICATE INTEGRATED - Mr. Ikhsan; Vellayati Hajad; Kemal Pasya (DIA: Jurnal Administrasi Publik, 2020)
This paper describes local government innovations that are part of the Civil Service and Civil Registry (Dukcapil) reform. Arrangement of birth certificate and death certificate integrated village fund is an innovation policy in West Aceh Regency which is abbreviated as Aklamasi Dansa. The issue of legal identity is still a problem in Indonesia, many people do not have a legal identity so it impacts all services provided by the government to the community. The policy of integrating birth certificates and death certificates is an innovation that brings government and society closer together. The Aklamasi Dansa has been running since 2017 and operates in the assisted village. This study uses a qualitative method with a case study approach. The informant of this research is the community as the recipient of services, the government of West Aceh as an innovator. The results showed that the Aklamasi Dansa policy have shown that they are capable of significantly increasing the percentage of ownership, as can be seen from the percentage of birth certificates in 2016, only 86% after the Aklamasi Dansa was implemented to be 94% in 2019. The same thing happened with the death certificate issued by Disdukcapil in West Aceh in 2016 only 86 death certificates after the aklamasi dansa went on to 1629 in 2019. The Aklamasi Dansa as one of the innovations in service to the community went very well in improving village data administration and making it easier for citizens to receive services in taking care of birth certificates and death certificates.